2020
DOI: 10.3389/fpls.2020.00443
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Effects of Chilling, Photoperiod, and Forcing Temperature on Flowering Phenology of Temperate Woody Plants

Abstract: The effects of winter chilling, spring forcing temperature, and photoperiod on spring phenology are well known for many European and North American species, but the environmental cues that regulate the spring phenology of East Asian species have not yet been thoroughly investigated. Here, we conducted a growth chamber experiment to test the effects of chilling (controlled by different lengths of exposure to natural chilling conditions), forcing temperature (12, 15, or 18°C) and photoperiod (14 or 10 h) on firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 61 publications
(81 reference statements)
1
18
0
Order By: Relevance
“…In comparison to the outdoor conditions (average temperature 3.7 °C), a much earlier flowering was observed in the climate chamber (average temperature 16.8 °C) for hazel (−69 days), alder (−35 days), and birch (−15 days), ordered by their harvesting dates beginning of December, end of January, and beginning of March. Wang et al ( 2020 ) observed similar trends in a climate chamber experiment on branches of six Asian woody species, where a 3 °C increase in spring temperature resulted in flowering advanced by 2.3 to 36.1 days, depending on the species. In the present study, an impact of the flowering time could be observed on the pollen amount produced, and on pollen characteristics for all investigated species.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In comparison to the outdoor conditions (average temperature 3.7 °C), a much earlier flowering was observed in the climate chamber (average temperature 16.8 °C) for hazel (−69 days), alder (−35 days), and birch (−15 days), ordered by their harvesting dates beginning of December, end of January, and beginning of March. Wang et al ( 2020 ) observed similar trends in a climate chamber experiment on branches of six Asian woody species, where a 3 °C increase in spring temperature resulted in flowering advanced by 2.3 to 36.1 days, depending on the species. In the present study, an impact of the flowering time could be observed on the pollen amount produced, and on pollen characteristics for all investigated species.…”
Section: Discussionmentioning
confidence: 65%
“…From the literature, it is known that under warmer spring temperatures, flowering is generally accelerated (Fu et al 2012 ; Wang et al 2020 ). In the study of Fu et al ( 2012 ), potted saplings from beech, birch, and oak were treated with various temperature manipulations in climate chambers.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing interest in the role of photoperiod on spring phenology ( Körner and Basler, 2010 ; Polgar and Primack, 2011 ; Way and Montgomery, 2015 ). However, the effects of photoperiod are variable ( Cooke et al, 2012 ; Wang et al, 2020 ) and certainly not as important as temperatures ( Laube et al, 2014 ; Harrington and Gould, 2015 ; Nanninga et al, 2017 ). The claimed photoperiod effects are often confounded with temperature effects, i.e., longer photoperiods are associated with greater forcing temperatures ( Nienstaedt, 1967 ; Worrall and Mergen, 1967 ; Falusi and Calamassi, 1990 ; Heide, 1993 ; Caffarra and Donnelly, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was justified because of the high correlation between them but, as such, their effects ended up being confounded. Plants' mechanisms of recognition of the photoperiod and temperature environmental cues can differ [95][96][97] but there is mounting evidence of complex interactions among them. Indeed, photoperiod sensitivity genes that may trigger flowering response can be intricately-linked to temperature shifts, such as in winter wheat, where they work in concert with vernalization (cold response) genes [98].…”
Section: Discussionmentioning
confidence: 99%